Comparison of tramadol and pethidine for control of shivering in regional anesthesia - Paul, Cherish; Paul, John (International Journal of Research in Medical Sciences, 2017)
Background: Shivering is a common problem faced by anaesthesiologists in the intraoperative as well as post-operative period. It occurs during both general anesthesia and regional anesthesia, but is more frequent and troublesome during regional anesthesia. There are many pharmacological and other methods to tackle this issue. Not many studies have compared between pharmacological agents that control shivering. Methods: This randomized, prospective study conducted in 80 adult patients, was designed to explore the efficacy and potency of Tramadol in comparison to Pethidine for control of shivering under regional anesthesia. Patients received Tramadol or Pethidine in a dose of 0.5 mg/kg intravenously after the appearance of shivering. Disappearance and recurrence of shivering, sedation as well as haemodynamics were observed at scheduled intervals Results: The complete disappearance of shivering took a mean 4.5 minutes in Tramadol group while 8 minutes in pethidine group (p value<=0.05). Tramadol was more potent than Pethidine with respect to control of shivering and its recurrence. Conclusions: Intravenous Tramadol is qualitatively superior to Pethidine for control of shivering after regional anesthesia.